The sky's the limit. - Hogge, Becky (New Statesman, 2008)
In this article the author discusses aspects of cloud computing. She describes the advantage of such a system would confer on software developers who would benefit from the Internet server capacity that such a system would promote. She notes that cloud computing would lead to significant increases in Internet application speeds.